Interaction of organic cation transporter 3 (SLC22A3) and amphetamine - Zhu, Hao-Jie (2010)
The organic cation transporter (OCT) 3 is widely expressed in various organs in humans, and involved in the disposition of many exogenous and endogenous compounds. Several lines of evidence have suggested that OCT3 expressed in the brain plays an important role in the regulation of neurotransmission. Relative to wild-type (WT) animals, Oct3 knockout (KO) mice have displayed altered behavioral and neurochemical responses to psychostimulants such as amphetamine (AMPH) and methamphetamine. In the present study, both in vitro and in vivo approaches were utilized to explore potential mechanisms underlying the disparate neuropharmacological effects observed following AMPH exposure in Oct3 KO mice. In vitro uptake studies conducted in OCT3 transfected cells indicated that dextroamphetamine (d-AMPH) is not a substrate of OCT3. However, OCT3 was determined to be a high-capacity and low-affinity transporter for the neurotransmitters dopamine (DA), norepinephrine (NE), and serotonin (5-HT). Inhibition studies demonstrated that d-AMPH exerts relatively weak inhibitory effects on the OCT3-mediated uptake of DA, NE, 5-HT, and the model OCT3 substrate 4-(4-(dimethylamino)styryl)-N-methylpyridinium iodide. The IC(50) values were determined to be 41.5 ± 7.5 and 24.1 ± 7.0 μM for inhibiting DA and 5-HT uptake, respectively, while 50% inhibition of NE and 4-(4-(dimethylamino)styryl)-N-methylpyridinium iodide uptake was not achieved by even the highest concentration of d-AMPH applied (100 μM). Furthermore, the disposition of d-AMPH in various tissues including the brain, liver, heart, kidney, muscle, intestine, spleen, testis, uterus, and plasma were determined in both male and female Oct3 KO and WT mice. No significant difference was observed between either genotypes or sex in all tested organs and tissues. Our findings suggest that OCT3 is not a prominent factor influencing the disposition of d-AMPH. Additionally, based upon the inhibitory potency observed in vitro, d-AMPH is unlikely to inhibit the uptake of monoamines mediated by OCT3 in the brain. Differentiated neuropharmacological effects of AMPHs noted between Oct3 KO and WT mice appear to be due to the absence of Oct3 mediated uptake of neurotransmitters in the KO mice.